Experience with Tissue Bank Services in 2014 and 2020 in Turku, Finland - Tikkala Santtu; Tirkkonen Kari; Ekman Elina; Lehtimäki Kaisa (Elsevier Inc., 2025)
Background: The objective of a musculoskeletal tissue bank is to collect, test, store, and provide musculoskeletal tissue allografts required in orthopedic procedures. Strict exclusion criteria are followed when selecting suitable cadaver musculoskeletal tissue donors, and the allografts are procured under sterile conditions to avoid bacterial contamination. Tissue banking in Turku, Finland, began in 1972, and tissue bank services were last reviewed in 2003. This study aimed to review the operation of the musculoskeletal tissue bank in Turku, Finland, between 2014 and 2020 and to analyze the number, types, and contamination rate of the allografts procured from the cadaver donors. Potential donor-related factors causing bacterial contamination of the allografts and whether potential musculoskeletal tissue donors were overlooked among multiorgan donors were also studied.
Methods: A retrospective review of all cadaver musculoskeletal tissue donors used in the Hospital District of Southwest Finland Tyks Orto Musculoskeletal Tissue Bank during the study period was conducted, and data on the procured allograft was collected and presented. The donors were selected among patients treated in the intensive care unit (ICU) of Turku University Hospital (TYKS).
Results: A total of 28 cadaver donors were used, and 636 allografts were procured between 2014 and 2020. The bacterial contamination rate was 2.5%, which was lower than that in the previous international literature. The median treatment time in the ICU was significantly longer, and the median value of the highest C-reactive protein level was significantly higher in the group of donors with positive allograft bacterial cultures.
Conclusions: The bacterial contamination rate in the tissue bank was low on an international scale. Some suitable musculoskeletal tissue donors were overlooked among multiorgan donors.
Copyright © 2023 The Author(s). Published by Elsevier Inc. All rights reserved.